The vegetarian athlete - Cox, G. (International SportMed Journal, 2001)
To date, the advantages and disadvantages of vegetarian eating by athletes have not been fully investigated. Studies are warranted to determine the potential benefits, if any, of a long-term vegetarian diet on exercise performance. A well-planned lacto-ovovegetarian or vegan diet will meet the nutrient requirements of most athletes. A poorly planned vegetarian or near-vegetarian diet, however, might provide insufficient energy and fail to meet daily nutrient needs. Nutritious, energy-dense vegetarian meat alternatives should be included daily to ensure adequate energy and nutrient intake. The high carbohydrate content of most vegetarian diets is conducive to restoring and maintaining adequate glycogen stores in athletes with high daily carbohydrate requirements. Although animal foods are good sources of protein, iron, zinc, and vitamin B12, and dairy products are rich sources of calcium, alternative sources are available to vegetarian athletes. Food sources fortified with vitamin B12 should be included in a vegan diet. Further research is required to better understand the influence of long-term vegetarian diets on menstrual status in female athletes.